Photoactivity of Titanium Dioxide Foams. (10th April 2018) - Jami, Maryam; Dillert, Ralf; Suo, Yanpeng; Bahnemann, Detlef W.; Wark, Michael
Abstract : TiO2 foams have been prepared by a simple mechanical stirring method. Short-chain amphiphilic molecules have been used to stabilize colloidal suspensions of TiO2 nanoparticles. TiO2 foams were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), UV-vis absorption spectroscopy, and scanning electron microscopy (SEM). The photoassisted oxidation of NO in the gas phase according to ISO 22197-1 has been used to compare the photoactivity of the newly prepared TiO2 foams to that of the original powders. The results showed that the photoactivity is increased up to about 135%. Foam structures seem to be a good means of improving the photoactivity of semiconductor materials and can readily be used for applications such as air purification devices.